Statistical analysis plan for a pragmatic randomised controlled trial comparing enhanced acceptance and commitment therapy plus ( +) added to usual aftercare versus usual aftercare only, in patients living with or beyond cancer: SUrvivors' Rehabilitation Evaluation after CANcer (SURECAN) trial - Clare Robinson; Trudie Chalder; Paul McCrone; Olivier Quintin; Evdoxia Gkaintatzi; Imran Khan; Stephanie J. C. Taylor; on behalf of the SURECAN GROUP (Trials)
Abstract Background The aim of the SURECAN trial is to evaluate a person-centred intervention, based on Acceptance and Commitment Therapy (ACT Plus ( +)), for people who have completed treatment for cancer with curative intent, but are experiencing poor quality of life. We present the statistical analysis plan for assessing the effectiveness and cost-effectiveness of the intervention in improving quality of life 1 year post randomisation. Methods and design SURECAN is a multi-centre, pragmatic, two-arm, partially clustered randomised controlled superiority trial comparing the effectiveness of ACT + added to usual care with usual aftercare. The target sample size is 344 (172 per arm), randomised centrally in a 1:1 ratio. Results The primary outcome is the total score of the Functional Assessment of Cancer Therapy scale-General (FACT-G) at 52 weeks, analysed using a partially nested mixed-effects model with heteroskedastic error terms. Secondary outcomes include scores at 16 and 52 weeks: FACT-G subscales; Fear of Cancer Recurrence Inventory (FCR4); positive and negative Impact of Cancer scales (IOCv2); Hospital Anxiety and Depression scale (HADS); Chalder Fatigue Scale (CFQ); and physical activity, measured on a modified version of the Godin scale. Health economic analyses will determine the incremental cost-effectiveness ratio (ICER) in terms of quality-adjusted life years (QALYs) derived from the Euroqol 5-Dimension 5-Level (EQ-5D-5L) compared to usual care at 52 weeks. Discussion This manuscript is the statistical analysis plan (SAP) and economic evaluation for the SURECAN trial. Any exploratory or post hoc analyses will be identified as such in the respective analysis report. Trial registration The trial was prospectively registered. ISRCTN: ISRCTN67900293. Registered on 09 December 2019.